Podróżując w głąb człowieczego wnętrza. Na marginesie twórczości Olgi Tokarczuk - Nęcka, Agnieszka (Postscriptum Polonistyczne, 2020)
The sketch focuses on two novels by Olga Tokarczuk (Flights and The Books of Jacob), seeking to show different ways of using the travel motif. In Tokarczuk’s case, in fact, this is not only about moving in the geographical space, but also about exploring one’s own self. The questions posed by the author of House of Day, House of Night are universal; addressing fundamental aspects, they reveal the 21st century human condition. The writer often uses the motif of time, of the book or of travelling as such, showing literature as a specific language of communication that makes it possible to experience other people’s lives.